2010 8th Annual Communication Networks and Services Research Conference 2010
DOI: 10.1109/cnsr.2010.47
|View full text |Cite
|
Sign up to set email alerts
|

Improving Heterogeneous Workload Performance in Server Virtualization through User Behavior Schedules

Abstract: One of the most attractive topics today is server virtualization. Virtualization is a method of running multiple independent virtual operating systems on a single physical computer. It is a way of maximizing physical resources to maximize the investment in hardware. This concept can help to consolidate servers, improve hardware utilization and reduce the consumption of power and physical space in the data center. However, in an environment where workloads share the underlying platforms, the problem of configur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…al. presented the improved performance on heterogeneous workload in server virtualization using user behavior scheduler [7]. They showed that the user behavior is different in each type of service and time.…”
Section: Related Workmentioning
confidence: 98%
“…al. presented the improved performance on heterogeneous workload in server virtualization using user behavior scheduler [7]. They showed that the user behavior is different in each type of service and time.…”
Section: Related Workmentioning
confidence: 98%